A qualidade do relacionamento como mediador da relação entre integração interorganizacional e o custo total de propriedade - Viana Júnior, Arildo Paulo (2014)
This research aims to propose and test a nomothetic model that can be used to analyze the relationship between the level of interorganizational integration and total cost of ownership, considering the relationship quality as a possible mediator of this re